Differentiated Cells Derived from Fetal Neural Stem Cells Improve Motor Deficits in a Rat Model of Parkinson's Disease. Issue 2 (December 2015) - Wang, Wei; Song, Hao; Shen, Aifang; Chen, Chao; Liu, Yanming; Dong, Yabing; Han, Fabin
Objective: Parkinson's disease (PD), which is one of the most common neurodegenerative disorders, is characterized by the loss of dopamine (DA) neurons in the substantia nigra in the midbrain. Experimental and clinical studies have shown that fetal neural stem cells (NSCs) have therapeutic effects in neurological disorders. The aim of this study was to examine whether cells that were differentiated from NSCs had therapeutic effects in a rat model of PD. Methods: NSCs were isolated from 14-week-old embryos and induced to differentiate into neurons, DA neurons, and glial cells, and these cells were characterized by their expression of the following markers: βIII-tubulin and microtubule-associated protein 2 (neurons), tyrosine hydroxylase (DA neurons), and glial fibrillary acidic protein (glial cells). After a 6-hydroxydopamine (6-OHDA)-lesioned rat model of PD was generated, the differentiated cells were transplanted into the striata of the 6-OHDA-lesioned PD rats. Results: The motor behaviors of the PD rats were assessed by the number of apomorphine-induced rotation turns. The results showed that the NSCs differentiated in vitro into neurons and DA neurons with high efficiencies. After transplantation into the striata of the PD rats, the differentiated cells significantly improved the motor deficits of the transplanted PD rats compared to those of the control nontransplanted PD rats by decreasing the apomorphine-induced turn cycles as early as 4 weeks after transplantation. Immunofluorescence analyses showed that the differentiated DA neurons survived more than 16 weeks. Conclusions: Our results showed that cells that were differentiated from NSCs had therapeutic effects in a rat PD model, which suggests that differentiated cells may be an effective treatment for patients with PD.